A Quarta Revolução Industrial e o papel dos sindicatos - Fernandes, Paulo Roberto (Universidade do Vale do Rio dos Sinos, 2021)
This Master's thesis has as its theme The Fourth Industrial Revolution and the Role of Trade Unions. The new industrial revolutionary period must be dealt with globally, as the effects affect all societies, since it is a dynamic phenomenon and does not have a definitive cradle, technologies are naturally merged and propagate in increasingly effective innovations, regardless of their naturalness. In this line of reasoning, it is time for the economic and professional categories to move towards the same horizon. However, with regard to the labor market, it presents volatility, ephemerality, suffers from dominations of the corporatist market and external interferences from emerging technologies. Therefore, in this context, it is worth a hard work of checks and balances, in the sense that companies and unions reduce the pace of rivalry, causing less technological unemployment created by the unbridled advancement of the technologies of the Fourth Industrial Revolution. Therefore, it is a current, real, social and economic issue. The unemployment rate in Brazil has been exaggeratedly expressive, especially since the first decade of the 21st century. There are several contributory causes for this phenomenon, however, the most significant has been that derived from industrial automation. There may also be disagreements between unions during collective bargaining, which makes the productive sector unfeasible, in this case, there will be a possible reduction in labor in the short term. In this sense, the present study aims to study the impacts of the Fourth Industrial Revolution and the Role of Trade Unions. In the preparation of this work, different methodological procedures were adopted: data analysis, graphs, statistics, all from the same source (IBGE); readings of books and periodicals, more interviews and debates enriched the research, however, the combination of empiricism with pragmatism seems to have been fundamental for the realization of this work. As for the results, in a first bias two important currents were found: the first, more optimistic, believes that in the implantation of machines with artificial intelligence, initially there will be a significant number of unemployed, but there will be a recovery, in the medium and long term, the generation of new, more qualified jobs. The other, more pessimistic, admits that unemployment is inevitable, although there is no way for a human being to compete with a robot, for example. Therefore, the balance will always be negative and growing in the artificially intelligent labor market. In other ways, other positions emerged, but not so different from the previous ones. However, there was a common feeling lodged in the Brazilian social fabric, that is, the fear that in the family - father, mother and children - they will no longer find jobs in their respective areas of study. Given the nature of the facts, it is essential to seek equalization paths to avoid unnecessary changes in the economic model and even greater inequalities between the working classes. It is time for a lot of solidarity and cooperation, the new model of worker needs knowledge and a lot of training, of the most varied types, always focusing on the demands of the constantly changing market. Colleges and universities, as a rule, are not trainers of labor for manufacturing companies. On the other hand, government institutions are also restricted due to a lack of resources, in addition to exaggerated bureaucracy. Thus, in the end, it must be inferred that the unions must continue in their secular mission, since teaching, training and education is, without a doubt, a sine qua non condition of union members, since they broke out and officially organized themselves to provide services to respective categories.
Keywords: Desemprego tecnológico; Tecnologias emergentes; Automação; Quarta revolução industrial; Inteligência artificial; Technological unemployment; Emerging technologies; Automation; Fourth industrial revolution; Artificial intelligence; ACCNPQ::Ciências Sociais Aplicadas::Direito